PENGARUH KUALITAS PELAYANAN PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA RESTORAN PUJANGGA STEAK AND COFFEE BUARAN - Via Fioka Alikasari; Leonardo Indra Vitaharsa (Human Capital Development, 2022)
This study has the aim of proving the effect of service quality, product quality and promotion on purchasing decisions at the Buaran Steak and Coffee Pujangga Restaurant. The population in this research is the buyers who come to the steak and coffee poet restaurant. The sampling technique used accidental sampling with a total of 100 respondents who came to the Pujangga and Steak Buaran restaurant. The data collection method used a questionnaire distributed to respondents. The data analysis used was a test of validity as well as reliability. Meanwhile for testing hypotheses such as Linear Regression. Multiple use of SPSS 25. The results of this study found that the quality of service does not have a significant impact on purchasing decisions and product quality and promotions have a significant impact on purchasing decisions, simultaneously service quality, product quality and promotions have a significant impact on purchasing decisions. Keywords : Quality of Service, Product Quality, Promotion of Purchasing Decision